Orientation of faults and their potential for reactivation in the present stress field in Finland - Koskinen, Paula (Helsingfors universitet, 2013)
Finland is situated in an intraplate area of low seismicity. Seismic hazard analyses require an assessment of regional maximum earthquake magnitude. One of the methods for estimating maximum magnitude is relating it to the dimensions of active faults. Intraplate earthquakes usually occur when pre-existing zones of weakness are reactivated in response to the ambient stress field. Because minor earthquakes rarely cause surface ruptures, the reactivated faults have to be studied by indirect means. In this study structural lineaments are used as proxies for old shear zones, faults and fractures. Their orientation with respect to the crustal stress field is determined in order to find potentially unstable faults. Firstly the orientation of the stress field is determined by reviewing literature and available data on crustal stress in Finland. The main force causing the compressive stress field in Fennoscandia is the spreading of the mid-Atlantic ridge, which is why the plate motion of Finland relative to North America is also taken into account. An estimate of 115° to 135° is reached for the azimuth of the maximum horizontal stress in Finland. The stress regime is mostly reverse (minimum principal stress is vertical) according to stress indicators and focal mechanisms. The lineaments are split into straight segments for azimuth calculation. The segments are then divided into optimal orientation categories based on the horizontal angle between the segment and the maximum horizontal stress. Reverse faulting takes place perpendicular to and normal as well as transfer faulting takes place parallel to the maximum horizontal stress. The direction of strike-slip faulting depends on the coefficient of internal friction, which is around 0.6 for solid rock and as low as 0.2-0.4 for pre-existing fractures. With these values the Coulomb failure criterion gives an optimal angle of 30° to 40° to the maximum horizontal stress for strike-slip faulting. The lineament segments with the different faulting categories are shown with ...